Ultrafast demagnetization in bulk nickel induced by X-ray photons tuned to Ni M 3 and L 3 absorption edges - Konrad J. Kapcia; Victor Tkachenko; Flavio Capotondi; Alexander Lichtenstein; Serguei Molodtsov; Przemysław Piekarz; Beata Ziaja (Scientific Reports, 2024)
Abstract Studies of light-induced demagnetization started with the experiment performed by Beaupaire et al. on Ni. Here, we present theoretical predictions for X-ray induced demagnetization of nickel, with X-ray photon energies tuned to its $$M_3$$ M 3 and $$L_3$$ L 3 absorption edges. We show that the specific feature in the density of states in the d-band of Ni, i.e., a sharp peak located just above the Fermi level, strongly influences the change of the predicted magnetic signal, making it stronger than in the previously studied case of X-ray demagnetized cobalt. It impacts also the value of Curie temperature for Ni. We believe that this finding will inspire dedicated experiments investigating magnetic processes in X-ray irradiated nickel and cobalt.